2019
DOI: 10.1148/ryct.2019180029
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Outcome in Idiopathic Pulmonary Fibrosis: Addition of Fibrotic Score at Thin-Section CT of the Chest to Gender, Age, and Physiology Score Improves the Prediction Model

Abstract: To assess the impact of adding thin-section CT-derived semiquantitative fibrotic score to gender, age, and physiology (GAP) model for predicting survival in idiopathic pulmonary fibrosis (IPF). Materials and Methods:In this retrospective study of 194 patients with IPF, primary outcome was transplant-free survival. Two thoracic radiologists visually estimated the percentage of reticulation and honeycombing at baseline thin-section CT, which were added to give fibrotic score. For analysis, fibrotic score cutoff … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
(41 reference statements)
0
9
0
1
Order By: Relevance
“…Ley et al (48) obtiveram um desempenho comparável ao do escore GAP substituindo o parâmetro da DLCO por um escore visual semiquantitativo de TCAR. Mais recentemente, Chahal et al (49) propuseram um modelo que adiciona uma avaliação tomográfica semelhante (escore visual semiquantitativo de fibrose acima ou abaixo de 25%) ao escore GAP, melhorando a predição do desfecho de sobrevida, especialmente em pacientes com doença em grau leve. Outras propostas de estadiamento multiparamétricas que incluem variáveis funcionais e avaliação tomográfica têm sido descritas para PIF relacionada a esclerose sistêmica, sarcoidose e outras manifestações.…”
Section: Avaliação De Gravidadeunclassified
See 1 more Smart Citation
“…Ley et al (48) obtiveram um desempenho comparável ao do escore GAP substituindo o parâmetro da DLCO por um escore visual semiquantitativo de TCAR. Mais recentemente, Chahal et al (49) propuseram um modelo que adiciona uma avaliação tomográfica semelhante (escore visual semiquantitativo de fibrose acima ou abaixo de 25%) ao escore GAP, melhorando a predição do desfecho de sobrevida, especialmente em pacientes com doença em grau leve. Outras propostas de estadiamento multiparamétricas que incluem variáveis funcionais e avaliação tomográfica têm sido descritas para PIF relacionada a esclerose sistêmica, sarcoidose e outras manifestações.…”
Section: Avaliação De Gravidadeunclassified
“…Ley et al 48 replaced DLCO with a visual semiquantitative HRCT score and reported that the resulting model had a performance that was comparable to that of the original GAP model. Chahal et al 49 evaluated the impact of adding a visual semiquantitative fibrotic score above or below 25% to the GAP model and found that the resulting model shows improved correlation with survival, especially in patients with mild disease. Other multidimensional indices including functional variables and CT evaluation have been proposed to stage systemic sclerosis-related fibrosing ILD, sarcoidosis, and other ILDs.…”
Section: Disease Severity Assessment Quantification and Follow-upmentioning
confidence: 99%
“…A recent study reported incorporating semi-quantitative fibrotic score from thin-section Computed tomography and GAP score provided a better prediction for survival in IPF. [ 24 ] However, these findings need to be confirmed in prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 26 ] The most dynamic system of gauging disease severity in IPF is likely to integrate biomarkers with longitudinal physiological data and changes identified on imaging. [ 10 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…The visually assessed extent of fibrosis on CT images is a predictor of survival in IPF patients [7][8][9][10]. Furthermore, the CT-derived extent of fibrosis can be used as a supplement to the GAP score to improve the capability of predicting survival [11], or as a substitute for DLCO in the GAP model [12]. However, the visual evaluation of fibrosis on CT can be limited by the subjective interpretation or degree of experience of the reader, causing inter-observer variation [13].…”
Section: Introductionmentioning
confidence: 99%